Industry View on Academic Programme Development: An Empirical Study. (31st May 2016) - Hussain, S.; Hanaysha, J.; Ibrahim, M.S.
Abstract: Automotive education trend in Malaysia is rapidly growing in both skills and academic based qualifications. There are various relevant programmes offered by public and private educational institutions in Malaysia. This study is conducted on Automotive Education Institution ("AEI") in East Coast Malaysia with an objective to acquire the automotive and services industry feedback prior to the new programmes development. A survey method was used for collecting the data from 323 respondents from various positions. The findings indicated the feedback from industry in various field and this could assist the AEI preparation of teaching and learning facilities including the academic staff.